Rise of the International international relations meets history - Devetak, Richard; Dunne, Timothy 1965- (Oxford University Press, 2024)
"Rise of the International brings together scholars of International Relations and History to capture the emergence and development of the thought, the relations, and the systems that have come to be called international in western discourse."
Keywords: Internationale Politik; Geschichtswissenschaft; Historical geography; Historische Geographie; International relations; Internationale Beziehungen; Social & cultural history; Sozial- und Kulturgeschichte; Aufsatzsammlung